Laparoscopic assisted hydrocelectomy of the canal of Nuck: a case report - Liming Wang; Taku Maejima; Susumu Fukahori; Katayose Shun; Daitaro Yoshikawa; Toru Kono (Surgical Case Reports)
Abstract Background Accurate diagnosis and complete resection of hydrocele of canal of Nuck (HCN) is still a challenge for surgeons. Case presentation A 28-year-old woman presented with a suspected inguinal hernia due to swelling in her right groin and was introduced for surgical treatment. Computed tomography scan revealed local cyst formation in the right groin and eliminated intestinal incarceration. In order to further confirm the diagnosis, we used laparoscopic exploration; after excluding a combined hernia, HCN was surgically removed using a conventional anterior peritoneal approach and a mesh patch repair was not needed. Postoperative pathology results showed no endometriosis or malignancy. Conclusions Laparoscopic assisted anterior approach provides both an accurate intraoperative diagnosis and a quick complete resection of HCN; it is the preferred treatment for women of childbearing age with pure HCN.